ANALISIS BAHAYA, LINTASAN, DAN SISTEM PROTEKSI TERHADAP POTENSI LONGSORAN TIPE JATUHAN BATU PADA LERENG BANGUNAN PELIMPAH BENDUNGAN TUGU, JAWA TIMUR - Muhammad Iqbal Hamidi; Imam Achmad Sadisun (JURNAL TEKNIK HIDRAULIK, 2021)
The construction of the Tugu Dam spillway does not escape the problem of slope instability, especially the rock fall type landslide as a result of the rock slope cutting work at STA+80. The purpose of this study was to determine the characteristics of the rock discontinuity area and the solutions needed to address the potential hazards of rock fall on the slopes of spillway structure. In this study, a semi-quantitative method conducted based on the Rockfall Hazard Rating System (RHRS) which is carried out by identifying outcrops on rock slopes. Determination of the rock fall trajectory, was conducted by statistical methods on rock mass based on changes in velocity when rocks roll, slide, and bounce. Geologically, the research area belongs to the Mandalika Formation. Based on the RHRS weighting, the total score on the STA+80 slope is 399, which means that the slope needs to be repaired or given safely with a moderate level of urgency. The rock fall trajectory modeling at the measurement location X = 121,875 has a kinetic energy of 973.14 kJ andesite and 72.59 kJ of volcanic breccia, for high results of 0.43 meters of andesite reflection and 2.04 meters of volcanic breccia, and velocity results translational velocity obtained at 33.8 m/s andesite and 8.67 m/s volcanic breccia. The potential for rock fall requires a safety system with a type of retained flexible barriers with a height of 5 meters that can be applied to the toe of the slope.Keywords: rock fall, discontinuity, trajectory, protection system, Tugu Dam